Representasi Perempuan dalam Narasi “Pengen Kurus” Iklan Rokok 76: Analisis Wacana Kritis Model Sara Mills - Muhammad Priadana; Syairal Fahmy Dalimunthe; Malan Lubis (Peneliti.net, 2026)
Advertisements, as a persuasive communication medium, not only convey information but also play a significant role in shaping social structures through language and visuals. In the context of cigarette advertisements where direct product displays are prohibited, advertisers use jokes, metaphors, and creative narratives to convey messages. This study examines the representation of women in the 76 cigarette advertisement